The International Criminal Court An Introduction - Novak, Andrew; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book is about the International Criminal Court (ICC), a new and highly distinctive criminal justice institution with the ability to prosecute the highest-level government officials, including heads of state, even in countries that have not accepted its jurisdiction. The book explores the historical development of international criminal law and the formal legal structure created by the Rome Statute, against the background of the Court$1 (Bs search for objectivity in a political global environment. The book reviews the operations of the Court in practice and the Court$1 (Bs position in the power politics of the international system. It discusses and clarifies all stages of an international criminal proceeding from the opening of the investigation to sentencing, reparations, and final appeals in the context of its restorative justice mission. Making appropriate comparisons and contrasts between the international criminal justice system and domestic and national systems, the book fills a gap in international criminal justice study.s
Preface -- The Organization of This Book -- Acknowledgments -- 1. Introduction -- 2. Origins of International Criminal Justice -- 3. The Rome Statute of the International Criminal Court -- 4. Jurisdiction of the Court -- 5. Investigation and Prosecution -- 6. Sentencing, Punishment, and Appeals -- 7. Current Controversies -- Discussion Questions -- Further Reading -- Reference List -- About the Author -- Index.
Keywords: Social sciences; Law -- Philosophy; Law; Private international law; Conflict of laws; International law; Comparative law; International criminal law; Criminology; Social Sciences; Criminology & Criminal Justice; Private International Law, International & Foreign Law, Comparative Law; International Criminal Law; Fundamentals of Law; Electronic books